The Representation of Women in Ramón Otero Pedrayo’s Plays and Film Scripts - Tato Fontaíña, Laura (Madrygal. Revista de Estudios Gallegos, 2016)
The article explores the depiction of women in Ramón Otero Pedrayo’s plays and film scripts whilst analysing the evolution of his female characters and how they compare with the female characters in his earlier prose fiction. Otero Pedrayo’s plays comprise a diverse collection of texts from 1929 to 1952, including a rural tragedy (A Lagarada), sixteen avant-garde plays (Teatro de Máscaras), a street theatre play (O Desengano do Priorio), and ten short plays published in the press. The analysis focuses particular attention on the author’s screenplays Camino de Santiago, Rosalía and three shorter texts. Written during the Franco regime, Otero Pedrayo’s film scripts reveal a shift in perspective in relation to the role of women in his work, leaving behind the negative, peripheral role associates with his female characters prior to 1936. The new depiction of an educated, cosmopolitan female university student reflected the transformation in Galician society witnessed by the author at that time.